2006
DOI: 10.1016/j.amjhyper.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Myocardial Functional Reserve in Hypertension and Diabetes Mellitus Without Coronary Artery Disease: Searching for the Possible Link With Congestive Heart Failure in the Myocardial Doppler in Diabetes (MYDID) Study II

Abstract: The addition of DM to HTN has a negative effect on LV systolic and diastolic functions. A depressed myocardial functional reserve might be postulated as one of the pathophysiologic mechanisms for the excessive occurrence of congestive heart failure in patients with DM or HTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…Although patients with angina, a history of CAD, inducible ECG changes, or rest or stress wall motion abnormalities were ineligible, the likelihood that CAD could not be excluded by the limited sensitivity of stress echocardiography in patients undergoing submaximal exercise, and the potential influence of coronary microvascular dysfunction, could not be entirely excluded either. Hypertension is independently associated with impaired left ventricular functional reserve, and shows a negative effect on left ventricular systolic and diastolic function 6. Therefore, it may not be easy to tease out the exact impact of hypertension on DFR in this study, although no significant difference in left ventricular DFR was observed in patients with or without hypertension.…”
Section: Discussionmentioning
confidence: 73%
“…Although patients with angina, a history of CAD, inducible ECG changes, or rest or stress wall motion abnormalities were ineligible, the likelihood that CAD could not be excluded by the limited sensitivity of stress echocardiography in patients undergoing submaximal exercise, and the potential influence of coronary microvascular dysfunction, could not be entirely excluded either. Hypertension is independently associated with impaired left ventricular functional reserve, and shows a negative effect on left ventricular systolic and diastolic function 6. Therefore, it may not be easy to tease out the exact impact of hypertension on DFR in this study, although no significant difference in left ventricular DFR was observed in patients with or without hypertension.…”
Section: Discussionmentioning
confidence: 73%
“…Assessment of myocardial strain and SR has been used to identify early systolic impairment in arterial hypertension [89], asymptomatic mitral regurgitation [90], pulmonary hypertension [91], rejection after HTX [92], congenital cardiac abnormalities [93], obesity [94], subclinical atherosclerosis [95], and in a number of systemic diseases [96,97]. Strain can discriminate between hypertensive cardiomyopathy and nonobstructive hypertrophic cardiomyopathy [98].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…However, there may be diabetes-specific accelerated forms of atherosclerosis with enhanced thrombogenicity (57). In the literature, a case is being made for the existence of a distinct form of cardiac dysfunction that has been termed "diabetic cardiomyopathy" (58,59). A universal finding among diabetics is a high prevalence of abnormal prolongation of the corrected QT (QTc) interval from the ECG (60).…”
Section: Diabetes As a Potential Predictor Of Sudden Cardiac Death Riskmentioning
confidence: 99%